2021
DOI: 10.1038/s41598-020-80322-0
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites changes in germinated barley and its relationship to anti-wrinkle activity

Abstract: The purpose of this research was to identify metabolite change during barley (Hordeum vulgare) germination and reveal active principles for the anti-wrinkle activity. Barley was germinated with deionized water (DW) and mineral-rich water (MRW) for the comparison of the effect of mineral contents on the metabolites changes during germination. The effects of germinated barley extracts (GBEs) on collagen production and collagenase inhibition were evaluated in vitro using human dermal fibroblasts (HDFs). A pronoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Mineral‐rich water is reported by changes metabolites for mineral contents compared to distilled water 16 . Germinated barley extracts with mineral‐rich water in Jeju revealed to be associated with the increase of procyanidin and prodelphinidin, indicating the anti‐wrinkle activity 9 . It should be noted that the content of mineral water in Jeju affects the antioxidant activity and anti‐aging effects, means that its utilization value is higher than that of other water resources 16 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mineral‐rich water is reported by changes metabolites for mineral contents compared to distilled water 16 . Germinated barley extracts with mineral‐rich water in Jeju revealed to be associated with the increase of procyanidin and prodelphinidin, indicating the anti‐wrinkle activity 9 . It should be noted that the content of mineral water in Jeju affects the antioxidant activity and anti‐aging effects, means that its utilization value is higher than that of other water resources 16 .…”
Section: Discussionmentioning
confidence: 98%
“…16 Germinated barley extracts with mineral-rich water in Jeju F I G U R E 2 Effects of type I collagen on Angelica gigas Nakai root extracts in human dermal fibroblasts revealed to be associated with the increase of procyanidin and prodelphinidin, indicating the anti-wrinkle activity. 9 It should be noted that the content of mineral water in Jeju affects the antioxidant activity and anti-aging effects, means that its utilization value is higher than that of other water resources. 16 Previously, we confirmed the anti-aging effects of A. gigas Nakai cultured in mineral-rich water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the pre‐treatment with β‐glucan could alleviate the gastric mucosal damage induced by ethanol [54] . Anti‐wrinkle and antimicrobial in addition to behavioral study are also specific activities measured for the ethanolic extracts [49,50,55] . Lee et al .…”
Section: Solvents Used In the Extraction Of Barleymentioning
confidence: 99%
“…[54] Anti-wrinkle and antimicrobial in addition to behavioral study are also specific activities water China preventing chronic inflammation in cardiovascular diseases, Anti-oxidant (ORAC-FRAP) [30] water China DPPH and NO radical scavenging activity assays [17] measured for the ethanolic extracts. [49,50,55] Lee et al…”
Section: Ethanol Extractmentioning
confidence: 99%